Nghiên cứu chế tạo tấm compozit gốm chống đạn - Khiêm, Vũ Đình; Thiếp, Lê Trọng; Hà, Nguyễn Quốc; Anh, Lê Hoài (Vietnam Journal of Chemistry, 2014)
This paper presented the effect of the ratio, temperature and technology on physico-mechanical. Characteristics of ceramic material reinforcing composites for personal body armors production [4]. It was shown that when using 28 wt% of fine aluminium oxide of 1.2 mm size, the flexural strength increased to 28%, Mohr’s hardness increased from 6.1 to 8.5 and density-from 1.77 g/cm3 to 3.10 g/cm3. The ratio DER-331/DETA and DER-331/Kevlar-129 for productions of ceramic composites armors level III in industrial scale was studied. It showed that the obtained ceramic composite armors could be used against AK 47 bullet with speed of 715 m/s at 15 m distance [5].